Perkembangan pengajian Ilmu mukhtalif Al-hadith: Kajian ketokohan Al-Marbawi - Mohd Solleh Ab Razak; Mohd Nor Adzhar Ibrahim; Khairol Ikhwan @ Mohd Fithri Khoza (Universiti Sains Islam Malaysia, 2025)
Mukhtalif al-hadith is one of the crucial branches in the science of hadis, as it serves as a tool for resolving apparent contradictions in hadis. Recognizing its importance, Muhammad bin Idris al-Marbawi, a renowned scholar of hadis in the Malay Archipelago, dedicated special attention to discussing this discipline in his works. His ability to resolve contradictions between hadiss highlighted his expertise in the science of mukhtalif al-ḥadīth. Thus, this study aims to examine the development of al-Marbawi's contributions to the study of mukhtalif al-ḥadīth. To achieve this objective, a qualitative research method was employed through a literature review. Information related to al-Marbawi's contributions in the field of mukhtalif al-ḥadīth was collected and analyzed using inductive and deductive methods. The findings of this study reveal that al-Marbawi's journey in seeking knowledge, coupled with his diligence in mastering the science of mukhtalif al-ḥadīth, qualified him to be recognized as a prominent hadis scholar. From the outset, he received systematic education in hadis studies at Pondok Tuan Hussain Kedah before pursuing further studies in mukhtalif al-ḥadīth at Al-Azhar University. In Egypt, Al-Marbawi also engaged in informal studies through talaqqi sessions at mosques around Cairo to broaden his existing knowledge spectrum. Among al-Marbawi's key teachers who significantly influenced his prominence in the field of mukhtalif al-ḥadīth were Muḥammad bin Ibrāhīm al-Samālūṭī, Muḥammad ‘Alī al-Mālikī, and Yūsuf al-Ḥāwī.